Ketorolac and post-tonsillectomy hemorrhage in pediatric population - Gonçalves, Ana Isabel C. (2020)
Objectives: To assess the risk of post-tonsillectomy hemorrhage associated with the use of ketorolac in children undergoing tonsillectomy. Material and Methods: Retrospective study of children undergoing tonsillectomy between January 2015 and December 2019. Data were collected regarding age, sex, surgical indication, surgery performed, surgical technique, surgeon's experience, hemostasis method, occurrence of postoperative bleeding and its characterization, treatment instituted and the administration or not of ketorolac in the immediate postoperative period.  Results: Included 964 children, 48% female and 52% male, from 2 to 18 years old. Of these, 902 (93.6%) did not receive ketorolac, while 62 (6.4%) received a single dose. The incidence of bleeding in the group with administered ketorolac was 9.7% vs. 4.8% in the group without ketorolac (p = 0.123). The rate of primary bleeding was 50% in the group that took ketorolac vs. 18.6% in the group without ketorolac (p = 0.117). In children with hemorrhage, the need for surgical review of hemostasis was 50% in the group taking ketorolac vs. 18.6% in the group that did not take ketorolac (p = 0.117).  Conclusions: There was no statistically significant impact of the use of ketorolac on postoperative bleeding, although the results tend to point to an increased risk of bleeding. Further studies are needed, namely prospective and with homogeneous groups.